Lagrangian reduction by stages - Cendra, Hernán, 1943- (Memoirs of the American Mathematical Society, 2001)
Introduction Preliminary constructions The Lagrange-Poincare equations Wong's equations and coordinate formulas The Lie algebra structure on sections of the reduced bundle Reduced tangent bundles Further examples The category $\mathfrak{LP}^*$ and Poisson geometry Bibliography.